PtNPs/PEDOT:PSS-Modified Microelectrode Arrays Reveal Electrophysiological Activities of Different Neurons in Medial Amygdala of Mice Under Innate Fear - Fan, Penghui; Song, Yilin; Lu, Botao; Wang, Yiding; Dai, Yuchuan; Xie, Jingyu; He, Enhui; Xu, Zhaojie; Yang, Gucheng; Mo, Fan; Liu, Juntao; Wang, Mixia; et al. (Frontiers in Neuroscience, 2022)
The medial amygdala (MA) plays an important role in the innate fear circuit. However, the electrophysiological mechanism of MA for processing innate fear needs to be further explored. Here, we fabricated microelectrode arrays (MEAs) with detecting sites arranged to match the location and shape of MA in mice, and detected the electrophysiology in freely behaving mice under 2-methyl-2-thiazoline (2MT)-induced fear. Metal nanoparticles and conductive polymers (PtNPs/PEDOT:PSS) was modified onto the MEAs to improve the detection performance. After modification, the impedance magnitude and phase of electrodes were decreased to 27.0 ± 5.9 kΩ and -12.30 ± 0.52° respectively, leading to a better signal-to-noise ratio of 10. MEAs were then implanted into the MA of mice, and the electrophysiology and behavioral characteristics were synchronously recorded and analyzed. The results showed that 2MT induced strong defensive behaviors of mice, accompanied by increases in the average spike firing rate and LFP (Local Field Potential) power of MA neurons. Statistics showed that about 87% of glutamatergic neurons and 35% of GABAergic neurons were significantly activated under innate fear. The firing rate of some neurons had a good linear correlation with the freezing rate, which may provide evidence for MA encoding fear emotion.